Reducing conditions on barium absorption in rice plants cultured in BaSO4-enriched soil - Marcio Osvaldo Lima Magalhães (Acta Scientiarum. Agronomy, 2014)
To evaluate the possible solubilization of barium sulfate in soils under reducing conditions and its effects on barium bioavailability, an Oryza sativa pot trial was established. Increasing barium doses and two redox potential conditions were evaluated. The geochemical fractionation data demonstrated that reducing conditions led to an increase in the levels of more labile forms of barium and a reduction in more stable forms. Furthermore, higher doses of barium were found to have a negative impact on grain production. The highest levels of barium accumulation in the leaves, roots, and grains were observed with the highest barium dose under reducing conditions. These results demonstrate that reducing conditions increased barium bioavailability and absorption by rice plants.